Cobalt-based sulfide self-supporting catalytic material as well as preparation method and application thereof
By growing cobalt-based sulfide self-supporting catalytic materials with Co9S8/CuCo2S4 heterostructure on the substrate in situ, the problems of high cost and poor stability of existing cobalt-based catalytics are solved, and efficient oxygen precipitation and oxygen are achieved Reduce catalytic activity and significantly improve the cycle life of zinc air batteries.
Patent Information
- Application Number
- CN202411345239.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing cobalt-based catalysts have high preparation cost and poor stability, making it difficult to meet the requirements of catalytic performance of oxygen precipitation reaction (OER) and oxygen reduction reaction (ORR) in zinc air batteries.
Using cobalt-based sulfide self-supported catalytic material, the preparation process is simplified by the hydrothermal method and reduced energy consumption and cost.
The dual-function catalytic activity of the material is improved, and the overall conductivity and stability of the positive electrode of the battery is enhanced, which is significantly better than the cycle life of commercial 20% Pt/C+RuO2 catalysts.
Smart Images

Figure CN119419283A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to a cobalt-based sulfide self-supporting catalytic material, a preparation method and an application thereof. Background Art
[0002] Zinc-air battery is an energy storage and conversion device that uses metallic zinc as the negative electrode and directly obtains oxygen from the air as the positive electrode reactant. Its theoretical energy density is as high as 1086 Wh / kg. It has the characteristics of low cost, high energy density, long cycle life, and environmental friendliness. It has attracted much attention in the field of electrochemical energy storage.
[0003] Although zinc-air batteries have high theoretical energy density and many advantages, their commercial application still faces huge challenges. The high polarization phenomenon and rapid attenuation problem of the air electrode cause the actual energy density of zinc-air batteries to be far lower than theoretical expectations. This bottleneck is mainly due to the slow reaction kinetics of the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR), which seriously restricts the overall performance of the battery. Therefore, it is necessary to explore efficient bifunctional catalysts to reduce the overpotential of the ORR and OER processes, thereby improving the energy conversion efficiency.
[0004] Among various electrocatalytic materials, cobalt-based sulfides are low-cost, stable and have good electrocatalytic activity, making them ideal materials to replace precious metal-based catalysts. However, the poor intrinsic conductivity and limited catalytic active sites of single cobalt-based sulfides hinder their widespread application in the field of zinc-air batteries. In the related art, Chinese patent CN111841577A discloses a method for preparing a sheet-like copper-cobalt bimetallic sulfide catalytic material, which utilizes the synergistic effect between copper and cobalt atoms to enhance the catalytic activity of the material in the oxygen evolution reaction (OER). However, this method uses octylamine as an organic solvent, which is highly toxic and poses potential hazards to the environment and human health. Patent CN110790318A reports a method for preparing a Co9S8 / MoS2 multi-level structure composite material, which uses interfacial chemical interaction or electrical coupling as a synergistic effect between the two components to improve the catalytic performance and stability of the material to a certain extent. However, its preparation process requires high-temperature calcination, high energy consumption and high cost, and its catalytic performance in the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) is still insufficient to meet actual needs.
[0005] In summary, the cobalt-based sulfide catalysts currently used in zinc-air batteries have high preparation costs and insufficient catalytic activity, and are still difficult to meet actual needs. Therefore, it is of great significance to develop a cobalt-based sulfide cathode material with efficient bifunctional catalytic activity and good cycle stability. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a cobalt-based sulfide self-supporting catalytic material, a preparation method and an application, aiming to solve the problems of high preparation cost and poor stability of cobalt-based catalysts in related technologies.
[0007] To solve the above technical problems, the present invention is implemented as follows: a cobalt-based sulfide self-supporting catalytic material includes a substrate and a Co9S8 / CuCo2S4 heterostructure supported on the substrate.
[0008] Furthermore, the Co9S8 / CuCo2S4 heterostructure is a hollow tubular structure.
[0009] Furthermore, the loading amount of the Co9S8 / CuCo2S4 heterostructure on the substrate is 0.5~3 mg·cm -2 .
[0010] The second aspect of the present invention provides a method for preparing a cobalt-based sulfide self-supporting catalytic material, comprising the steps of: S1: dissolving a metal compound and urea in water at room temperature to obtain a mixed solution, wherein the metal compound is a cobalt metal compound and a copper metal compound; S2: placing the substrate in the mixed solution and reacting at a temperature of 80-150° C. for 4-12 hours to in-situ grow a double metal hydroxide precursor on the substrate; S3: placing the substrate with the double metal hydroxide precursor obtained in step S2 in a sulfide aqueous solution, and performing a hydrothermal sulfidation reaction at a temperature of 100-200°C for 3-12 hours to form a Co9S8 / CuCo2S4 heterostructure on the substrate, thereby obtaining the desired cobalt-based sulfide self-supporting catalytic material.
[0011] Furthermore, in step S1, the molar ratio of the metal compound to urea is 1:(0.5-10), and the molar ratio of the cobalt metal compound to the copper metal compound of the metal compound is 1:(0.05-0.5).
[0012] Furthermore, in step S1, the cobalt metal compound is any one of cobalt nitrate, cobalt chloride, cobalt acetate, cobalt sulfate and hydrates thereof; the copper metal compound is any one of copper nitrate, copper chloride, copper acetate, copper sulfate and hydrates thereof.
[0013] Furthermore, before step S2 is performed, the substrate is pretreated with an acidic solution.
[0014] Furthermore, in step S3, the sulfide is any one of sodium sulfide, thioacetamide, thiourea and hydrates thereof, and the concentration thereof is 0.05-0.5 mol / L.
[0015] The third aspect of the present invention provides a battery positive electrode, comprising the above-mentioned cobalt-based sulfide self-supporting catalytic material.
[0016] A fourth aspect of the present invention provides a zinc-air battery, comprising the above-mentioned battery positive electrode.
[0017] Compared with the prior art, the cobalt-based sulfide self-supporting catalytic material, preparation method and application thereof in the present invention have the following beneficial effects: (1) The cobalt-based sulfide self-supporting catalytic material of the present invention has abundant Co9S8 and CuCo2S4 heterogeneous interfaces, which promotes electron transfer at the interface, optimizes the adsorption capacity of oxygen intermediates, and helps to improve the bifunctional catalytic activity of the material in oxygen evolution reaction (OER) and oxygen reduction reaction (ORR); (2) The preparation method of the cobalt-based sulfide self-supporting catalytic material in the present invention only involves a simple two-step hydrothermal reaction. Compared with the use of organic solvents, the use of water as a solvent in the present invention is safer and more environmentally friendly. The hydrothermal temperature only needs to be 80-200°C, and the conditions are mild. (3) The preparation method of the cobalt-based sulfide self-supporting catalytic material of the present invention has high stability, and each preparation step can effectively control the morphology and composition of the product, ensuring the high stability and uniformity of the obtained material. The ratio of the dual-phase sulfide in the heterogeneous structure can be adjusted by controlling the concentration of the added cobalt and copper metal compounds; (4) The cobalt-based sulfide self-supporting catalytic material provided by the present invention is used as a battery positive electrode in a zinc-air battery. Its charge and discharge cycle life is significantly better than that of the commercial 20% Pt / C+RuO2 catalyst, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is an XRD pattern of the cobalt-based sulfide self-supporting catalytic material prepared in Example 1 of the present invention; Figure 2 is a scanning electron microscope (SEM) image of the cobalt-based sulfide self-supporting catalytic material prepared in Example 1 of the present invention; Figure 3 In Figure 3 (a) Figure 3 (b) and Figure 3 (c) is a transmission electron microscope (TEM) characterization image of the cobalt-based sulfide self-supporting catalytic material prepared in Example 1 of the present invention at different magnifications, Figure 3 (d) is the selected electron diffraction (SAED) pattern; Figure 4The LSV polarization curves of the oxygen reduction reaction catalytic activity test of the cobalt-based sulfide self-supporting catalytic material prepared in Example 1 of the present invention and the commercial 20% Pt / C catalyst are shown in FIG. 1 ; wherein the horizontal axis represents the reversible hydrogen electrode potential in volts (V); the vertical axis represents the current density in milliamperes per square centimeter (mA·cm -2 ); Figure 5 The LSV polarization curve of the catalytic activity test of the cobalt-based sulfide self-supporting catalytic material and the commercial RuO2 catalyst for oxygen evolution reaction prepared in Example 1 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential in volts (V); the ordinate represents the current density in milliamperes per square centimeter (mA cm -2 ); Figure 6 is an XRD pattern of the cobalt-based sulfide self-supporting catalytic material prepared in Example 2 of the present invention; Figure 7 is a scanning electron microscope (SEM) image of the cobalt-based sulfide self-supporting catalytic material prepared in Example 2 of the present invention; Figure 8 The LSV polarization curve of the oxygen reduction reaction catalytic activity test of the cobalt-based sulfide self-supporting catalytic material prepared in Example 2 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential in volts (V); the ordinate represents the current density in milliamperes per square centimeter (mA cm -2 ); Fig. 9 This is the LSV polarization curve of the catalytic activity test of the oxygen evolution reaction of the cobalt-based sulfide self-supporting catalytic material prepared in Example 2 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential, in volts (V); the ordinate represents the current density, in milliamperes per square centimeter (mA cm -2 ); Fig.10 is an XRD pattern of the cobalt-based sulfide self-supporting catalytic material prepared in Example 3 of the present invention; Fig.11 is a scanning electron microscope (SEM) image of the cobalt-based sulfide self-supporting catalytic material prepared in Example 3 of the present invention; Fig.12 This is a LSV polarization curve of the oxygen reduction reaction catalytic activity test of the cobalt-based sulfide self-supporting catalytic material prepared in Example 3 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential in volts (V); the ordinate represents the current density in milliamperes per square centimeter (mA cm -2 ); Fig.13This is the LSV polarization curve of the catalytic activity test of the cobalt-based sulfide self-supporting catalytic material for oxygen evolution reaction prepared in Example 3 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential in volts (V); the ordinate represents the current density in milliamperes per square centimeter (mA cm -2 ); Fig.14 The discharge curve and power density curve of the zinc-air battery assembled with the cobalt-based sulfide self-supporting catalytic material prepared in Example 1 of the present invention and the commercial 20% Pt / C+RuO2 catalyst; wherein the abscissa represents the current density in milliamperes per square centimeter (mA cm -2 The left vertical axis represents voltage in volts (V); the right vertical axis represents power density in milliwatts per square centimeter (mW cm -2 ); Fig.15 The cobalt-based sulfide self-supporting catalytic material prepared in Example 1 of the present invention and the commercial 20% Pt / C+RuO2 catalyst in the zinc-air battery at 10 mA·cm -2 Cycle life test chart under current density; the horizontal axis represents time in hours (h); the vertical axis represents voltage in volts (V). DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0020] This embodiment provides a method for preparing a cobalt-based sulfide self-supporting catalytic material, comprising the steps of: S1: dissolving a metal compound and urea in water at room temperature to obtain a mixed solution, wherein the metal compound is a cobalt metal compound and a copper metal compound; S2: placing the substrate in the mixed solution and reacting at a temperature of 80-150° C. for 4-12 hours to in-situ grow a double metal hydroxide precursor on the substrate; S3: placing the substrate with the double metal hydroxide precursor obtained in step S2 in a sulfide aqueous solution, and performing a hydrothermal sulfidation reaction at a temperature of 100-200°C for 3-12 hours to form a Co9S8 / CuCo2S4 heterostructure on the substrate, thereby obtaining the desired cobalt-based sulfide self-supporting catalytic material.
[0021] In this embodiment, a hydrothermal method was used to in-situ grow a double metal hydroxide precursor on a substrate, and then a simple in-situ hydrothermal sulfidation treatment was used to successfully prepare a Co9S8 / CuCo2S4 heterostructure supported on a substrate. Compared with the traditional method of physical coating of powder catalysts, in this embodiment, the self-supporting electrode in which the double metal sulfide is directly grown on the substrate has more structural advantages, avoids the use of binders, exposes more catalytic active sites, and improves the electrocatalytic performance of the material. The combination of the catalyst and the conductive substrate is more solid, which can effectively enhance the overall conductivity and stability of the battery positive electrode.
[0022] In the synthesis process of the material, based on the Kirkendall Effect, the solid needle-shaped double metal hydroxide precursor is used as a self-sacrificial template and converted into a hollow tubular structure through hydrothermal sulfurization. 2 + , Cu 2+ The radius is significantly smaller than S 2- The radius, Co 2+ , Cu 2+ The outbound transmission rate is greater than S 2- As the reaction proceeds, the double hydroxide precursor gradually dissolves and disappears, and the released metal ions react with the external S 2- The reaction forms a sulfide shell on the catalyst surface, and finally forms a hollow tubular Co9S8 / CuCo2S4 heterostructure. The hollow tubular morphology can effectively promote the transmission of electrons and the diffusion of oxygen, and provide a large number of catalytic active sites, thereby improving the catalytic efficiency, slowing down the volume change during the charge and discharge process, and enhancing the stability of the battery electrode material.
[0023] In step S1, the metal compound and urea are dissolved in water to obtain a mixed solution, comprising: The metal compound and urea were dissolved in deionized water, and stirred for 20 to 30 minutes to uniformly mix to obtain a mixed solution.
[0024] Preferably, in step S2, drying specifically comprises: drying at a temperature of 50-90° C. for 6-12 hours.
[0025] Preferably, in step S3, drying specifically comprises: vacuum drying at a temperature of 50-70° C. for 6-12 hours.
[0026] Furthermore, in step S1, the molar ratio of the metal compound to urea in the mixed solution is 1:(0.5-10), and the molar ratio of the cobalt metal compound to the copper metal compound in the metal compound is 1:(0.05-0.5).
[0027] Preferably, the molar ratio of the metal compound to urea is 1:(1-5).
[0028] Furthermore, in step S1, the cobalt metal compound is any one of cobalt nitrate, cobalt chloride, cobalt acetate, cobalt sulfate and hydrates thereof; the copper metal compound is any one of copper nitrate, copper chloride, copper acetate, copper sulfate and hydrates thereof.
[0029] The cobalt metal compound is preferably cobalt chloride hexahydrate, and the concentration of cobalt chloride hexahydrate is preferably 0.10-0.15 mol / L; the copper metal compound is preferably anhydrous copper chloride, and the concentration of anhydrous copper chloride is preferably 0.005-0.045 mol / L; the concentration of urea is preferably 0.15-0.75 mol / L.
[0030] Furthermore, before step S2 is performed, the substrate is pretreated with an acidic solution.
[0031] The substrate is pretreated with an acidic solution, wherein the substrate is any one of carbon cloth, carbon paper or nickel foam, and the acidic solution is at least one of hydrochloric acid, sulfuric acid and nitric acid.
[0032] Preferably, the substrate is made of carbon cloth, and the area of the substrate is 1-12 cm 2 The substrate is preferably a rectangular substrate with an area of 2 cm×3 cm.
[0033] Preferably, the acidic solution is a 65-68% concentrated nitric acid solution.
[0034] Further, the substrate is first pretreated with an acidic solution, comprising the steps of: Cutting the substrate, and immersing the substrate in an acid solution; Soak the substrate immersed in the acid solution at a temperature of 40-100°C for 6-24 hours; The substrate immersed in the acid solution is taken out, the substrate is cleaned, and the substrate is dried at a temperature of 50 to 90° C. for 6 to 12 hours to complete the pretreatment of the substrate.
[0035] Furthermore, in step S3, the sulfide is any one of sodium sulfide, thioacetamide, thiourea and hydrates thereof, and the concentration thereof is 0.05-0.5 mol / L.
[0036] Preferably, the sulfide is selected from sodium sulfide nonahydrate.
[0037] A specific embodiment of a method for preparing a cobalt-based sulfide self-supporting catalytic material is provided below.
[0038] Example 1 S1: prepare a carbon cloth substrate, cut the carbon cloth substrate into 2 cm×3 cm, and immerse the carbon cloth substrate in a 65-68 wt% concentrated nitric acid solution; The carbon cloth substrate placed in the concentrated nitric acid solution was placed in an oven at 60°C and soaked for 12 hours; The carbon cloth substrate placed in the concentrated nitric acid solution was taken out, and the carbon cloth substrate was washed three times with deionized water and anhydrous ethanol respectively, and the carbon cloth substrate was placed in a 60° C. forced air drying oven for 10 hours to complete the pretreatment of the carbon cloth substrate.
[0039] S2: Weigh 1.2848 g (5.4 mmol) of cobalt chloride hexahydrate and 0.0807 g (0.6 mmol) of anhydrous cupric chloride, add 40 mL of deionized water, and stir magnetically for 10 min to obtain a mixed solution of metal compounds; then weigh 0.7207 g (12 mmol) of urea, add it to the above mixed solution of metal compounds, and stir magnetically for 10 min to obtain a mixed solution.
[0040] S3: transferring the mixed solution to a reactor, and placing the carbon cloth substrate vertically in the reactor; The reactor was placed in an oven and subjected to a hydrothermal reaction at 90°C for 6 h; After cooling to room temperature, the carbon cloth substrate was taken out, and the carbon cloth substrate was washed with deionized water and anhydrous ethanol respectively, and the carbon cloth substrate was placed in a 60° C. forced air drying oven for 10 h to obtain a double metal hydroxide precursor grown in situ on the carbon cloth substrate; S4: Weigh 2.8820 g (12 mmol) of sodium sulfide nonahydrate, add 30 mL of deionized water, and stir magnetically for 20 min to obtain a sulfide solution. Transfer the sulfide solution to a reactor and immerse the double hydroxide precursor in the sulfide solution. The reactor was placed in an oven and subjected to hydrothermal sulfidation at 150°C for 6 hours. After the reaction was completed, the reactor was cooled to room temperature. The product of the hydrothermal sulfidation reaction of the double hydroxide precursor was taken out, and the product was washed three times with deionized water and anhydrous ethanol respectively. The product was placed in a vacuum drying oven and vacuum dried at 60°C to obtain the desired cobalt-based sulfide self-supporting catalytic material. The cobalt-based sulfide self-supporting catalytic material included a carbon cloth substrate and a Co9S8 / CuCo2S4 heterostructure supported on the carbon cloth substrate. The loading amount of the Co9S8 / CuCo2S4 heterostructure on the carbon cloth substrate was 1.3 mg cm -2 .
[0041] The cobalt-based sulfide catalytic material prepared by the above method of this example was characterized by X-ray diffraction (XRD). Figure 1 is the XRD spectrum of the cobalt-based sulfide self-supporting catalytic material prepared in Example 1 of the present invention, according to Figure 1It can be seen that the XRD diffraction peaks of the cobalt-based sulfide self-supporting catalytic material correspond to the standard cards PDF#04-006-5681 and PDF#042-1450, indicating that there are two phases of sulfides, Co9S8 and CuCo2S4, in the material, and no other impurity phases.
[0042] like Figure 2 As shown, Figure 2 This is a scanning electron microscope (SEM) image of the cobalt-based sulfide self-supporting catalytic material prepared in Example 1. It can be seen that the prepared cobalt-based sulfide self-supporting array is a hollow tubular structure, which grows uniformly in all directions on the carbon cloth substrate.
[0043] Figure 3 is a transmission electron microscope (TEM) characterization image of the cobalt-based sulfide catalyst material prepared in Example 1, Figure 3 The morphology of Co9S8 / CuCo2S4 catalytic materials in (a) and (b) Figure 2 It is consistent with the structure of a hollow tube. The surface of the tube is rough and composed of many small particles, which is conducive to increasing the contact area between the catalytic material and the electrolyte. Figure 3 As shown in (c), the coexistence area of Co9S8 and CuCo2S4 can be observed in high-magnification TEM, and there is a clear interface between the two, which verifies the existence of Co9S8 / CuCo2S4 heterogeneous interface in the material. In addition, Figure 3 (d) is the selected electron diffraction (SAED) pattern, from which it can be observed that the diffraction rings belong to a polycrystalline structure, corresponding to the (311), (222), and (440) crystal planes of Co9S8 and the (113), (004), (115), and (044) crystal planes of CuCo2S4, respectively, further confirming the existence of two phases of Co9S8 and CuCo2S4 in the heterogeneous region.
[0044] Test Example 1: Oxygen electrocatalytic activity test In order to test the oxygen electrocatalytic activity of the electrode made of the cobalt-based sulfide self-supporting catalytic material, the cobalt-based sulfide self-supporting catalytic material prepared in the above Example 1 was electrochemically tested using a three-electrode system, and commercial 20% Pt / C and RuO2 precious metal catalysts were used as references.
[0045] The test conditions for the catalytic activity of oxygen reduction reaction were as follows: O2-saturated 0.1 M KOH solution was used as the electrolyte, Ag / AgCl electrode was used as the reference electrode, platinum wire was used as the counter electrode, and a glassy carbon electrode (5 mm in diameter) coated with the above-mentioned cobalt-based sulfide catalytic material was used as the working electrode. The loading of the cobalt-based sulfide catalytic material on the glassy carbon electrode during the test was 0.510 mg cm -2 , the rotating disk electrode speed is 1600 rpm.
[0046] The test conditions for the catalytic activity of oxygen evolution reaction are as follows: the electrolyte is 1M KOH solution, the reference electrode is Hg / HgO electrode, the counter electrode is platinum sheet, and the prepared cobalt-based sulfide self-supporting catalytic material is fixed with an electrode clamp and directly used as the working electrode. The loading of Co9S8 / CuCo2S4 heterostructure on the carbon cloth substrate is about 1.3 mg cm -2 .
[0047] Figure 4 LSV polarization curves of the oxygen reduction reaction catalytic activity test of the cobalt-based sulfide catalytic material prepared in Example 1 of the present invention and the commercial 20% Pt / C catalyst; wherein the abscissa represents the reversible hydrogen electrode potential in volts (V); the ordinate represents the current density in milliamperes per square centimeter (mA cm -2 ),like Figure 4 As shown, it can be seen that the half-wave potential of the oxygen reduction reaction of the cobalt-based sulfide catalytic material prepared in Example 1 is 0.790 V (vs. RHE), which is close to the half-wave potential of the commercial 20% Pt / C noble metal catalyst of 0.836 V (vs. RHE).
[0048] Figure 5 The LSV polarization curve of the catalytic activity test of the cobalt-based sulfide self-supporting catalytic material and the commercial RuO2 catalyst for oxygen evolution reaction prepared in Example 1 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential in volts (V); the ordinate represents the current density in milliamperes per square centimeter (mA cm -2 ),like Figure 5 As shown in the figure, it can be seen that the cobalt-based sulfide self-supporting catalytic material prepared in Example 1 has a high conductivity at 10 mA·cm -2 The overpotential at a current density of 264 mV is lower than the overpotential of 330 mV of commercial RuO2 noble metal catalyst, indicating that its oxygen evolution catalytic activity is significantly better than that of noble metal catalysts.
[0049] Example 2 S1: prepare a carbon cloth substrate, cut the carbon cloth substrate into 2 cm×3 cm, and immerse the carbon cloth substrate in a 65-68 wt% concentrated nitric acid solution; The carbon cloth substrate placed in the concentrated nitric acid solution was placed in an oven at 60°C and soaked for 12 hours; The carbon cloth substrate placed in the concentrated nitric acid solution was taken out, and the carbon cloth substrate was washed three times with deionized water and anhydrous ethanol respectively, and the carbon cloth substrate was placed in a 60° C. forced air drying oven for 10 hours to complete the pretreatment of the carbon cloth substrate.
[0050] S2: Weigh 1.3562 g of cobalt chloride hexahydrate and 0.0403 g of anhydrous cupric chloride, with a molar ratio of cobalt chloride hexahydrate to anhydrous cupric chloride being 1:0.05, add 40 mL of deionized water, and stir magnetically for 10 min to obtain a mixed solution of metal compounds; then weigh 0.7207 g of urea, add it to the above mixed solution of metal compounds, and stir magnetically for 10 min to obtain a mixed solution.
[0051] S3: transferring the mixed solution to a reactor, and placing the carbon cloth substrate vertically in the reactor; The reactor was placed in an oven and subjected to a hydrothermal reaction at 90°C for 6 h; After cooling to room temperature, the carbon cloth substrate was taken out, and the carbon cloth substrate was washed with deionized water and anhydrous ethanol respectively, and the carbon cloth substrate was placed in a 60° C. forced air drying oven for 10 h to obtain a double metal hydroxide precursor grown in situ on the carbon cloth substrate; S4: Weigh 2.8820 g (12 mmol) of sodium sulfide nonahydrate, add 30 mL of deionized water, and stir magnetically for 20 min to obtain a sulfide solution. Transfer the sulfide solution to a reactor and immerse the double hydroxide precursor in the sulfide solution. The reactor was placed in an oven and hydrothermally sulfurized at 150°C for 6 hours. After the reaction was completed, the reactor was cooled to room temperature, and the product of the hydrothermal sulfurization reaction of the double hydroxide precursor was taken out. The product was washed three times with deionized water and anhydrous ethanol respectively, and the product was placed in a vacuum drying oven and vacuum dried at 60°C to obtain the desired cobalt-based sulfide self-supporting catalytic material, which included a carbon cloth substrate and a Co9S8 / CuCo2S4 heterostructure loaded on the carbon cloth substrate.
[0052] The cobalt-based sulfide self-supporting catalytic material prepared by the above method of this example was characterized by X-ray diffraction (XRD). Figure 6 is the XRD spectrum of the cobalt-based sulfide self-supporting catalytic material prepared in Example 2 of the present invention, according to Figure 6 It can be seen that the XRD diffraction peaks of the cobalt-based sulfide catalytic material correspond to the standard cards PDF#04-006-5681 and PDF#042-1450, indicating that there are two phases of sulfide, Co9S8 and CuCo2S4, in the material, and no other impurity phases.
[0053] like Figure 7 As shown, Figure 7 This is a scanning electron microscope (SEM) image of the cobalt-based sulfide self-supporting catalytic material prepared in Example 2. It can be seen that the prepared cobalt-based sulfide self-supporting array is a hollow tubular structure, which grows uniformly in all directions on the carbon cloth substrate.
[0054] Test Example 2: Oxygen electrocatalytic activity test In order to test the oxygen electrocatalytic activity of the electrode made of the cobalt-based sulfide self-supporting catalytic material, the cobalt-based sulfide self-supporting catalytic material prepared in the above Example 2 was electrochemically tested using a three-electrode system. The test conditions and test steps for the oxygen reduction reaction catalytic activity test and the oxygen evolution reaction catalytic activity test were the same as those in Test Example 1.
[0055] Figure 8 LSV polarization curve of the oxygen reduction reaction catalytic activity test of the cobalt-based sulfide self-supporting catalytic material prepared in Example 2 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential in volts (V); the ordinate represents the current density in milliamperes per square centimeter (mA cm -2 ),like Figure 8 As shown, it can be seen that the half-wave potential of the oxygen reduction reaction of the cobalt-based sulfide catalytic material prepared in Example 2 is 0.758 V (vs. RHE).
[0056] Fig. 9 The LSV polarization curve of the oxygen evolution reaction catalytic activity test of the cobalt-based sulfide self-supporting catalytic material prepared in Example 2 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential, in volts (V); the ordinate represents the current density, in milliamperes per square centimeter (mA cm -2 ),like Fig. 9 As shown in the figure, it can be seen that the cobalt-based sulfide self-supporting catalytic material prepared in Example 2 has a high conductivity at 10 mA·cm -2 The overpotential is 271 mV at a current density of .
[0057] Example 3 S1: prepare a carbon cloth substrate, cut the carbon cloth substrate into 2 cm×3 cm, and immerse the carbon cloth substrate in a 65-68 wt% concentrated nitric acid solution; The carbon cloth substrate placed in the concentrated nitric acid solution was placed in an oven at 60°C and soaked for 12 hours; The carbon cloth substrate placed in the concentrated nitric acid solution was taken out, and the carbon cloth substrate was washed three times with deionized water and anhydrous ethanol respectively, and the carbon cloth substrate was placed in a 60° C. forced air drying oven for 10 hours to complete the pretreatment of the carbon cloth substrate.
[0058] S2: Weigh 0.9517 g of cobalt chloride hexahydrate and 0.2689 g of anhydrous cupric chloride, with a molar ratio of cobalt chloride hexahydrate to anhydrous cupric chloride being 1:0.5, add 40 mL of deionized water, and stir magnetically for 10 min to obtain a mixed solution of metal compounds; then weigh 0.7207 g of urea, add it to the above mixed solution of metal compounds, and stir magnetically for 10 min to obtain a mixed solution.
[0059] S3: transferring the mixed solution to a reactor, and placing the carbon cloth substrate vertically in the reactor; The reactor was placed in an oven and subjected to a hydrothermal reaction at 90°C for 6 h; After cooling to room temperature, the carbon cloth substrate was taken out, and the carbon cloth substrate was washed with deionized water and anhydrous ethanol respectively, and the carbon cloth substrate was placed in a 60° C. forced air drying oven for 10 h to obtain a double metal hydroxide precursor grown in situ on the carbon cloth substrate; S4: Weigh 2.8820 g (12 mmol) of sodium sulfide nonahydrate, add 30 mL of deionized water, and stir magnetically for 20 min to obtain a sulfide solution. Transfer the sulfide solution to a reactor and immerse the double hydroxide precursor in the sulfide solution. The reactor was placed in an oven and hydrothermally sulfurized at 150°C for 6 hours. After the reaction was completed, the reactor was cooled to room temperature, and the product of the hydrothermal sulfurization reaction of the double hydroxide precursor was taken out. The product was washed three times with deionized water and anhydrous ethanol respectively, and the product was placed in a vacuum drying oven and vacuum dried at 60°C to obtain the desired cobalt-based sulfide self-supporting catalytic material, which included a carbon cloth substrate and a Co9S8 / CuCo2S4 heterostructure loaded on the carbon cloth substrate.
[0060] The cobalt-based sulfide self-supporting catalytic material prepared by the above method of this example was characterized by X-ray diffraction (XRD). Fig.10 is the XRD spectrum of the cobalt-based sulfide catalyst material prepared in Example 3 of the present invention. Fig.10 It can be seen that the XRD diffraction peaks of the cobalt-based sulfide self-supporting catalytic material correspond to the standard cards PDF#04-006-5681 and PDF#042-1450, indicating that there are two phases of sulfides, Co9S8 and CuCo2S4, in the material, and no other impurity phases.
[0061] like Figure 7 As shown, Fig.11 This is a scanning electron microscope (SEM) image of the cobalt-based sulfide self-supporting catalytic material prepared in Example 3. It can be seen that the prepared cobalt-based sulfide self-supporting array is a hollow tubular structure, which grows uniformly in all directions on the carbon cloth substrate.
[0062] Test Example 3: Oxygen electrocatalytic activity test In order to test the oxygen electrocatalytic activity of the electrode made of the cobalt-based sulfide self-supporting catalytic material, the cobalt-based sulfide self-supporting catalytic material prepared in the above Example 3 was electrochemically tested using a three-electrode system. The test conditions and test steps for the oxygen reduction reaction catalytic activity test and the oxygen evolution reaction catalytic activity test were the same as those in Test Example 1.
[0063] Fig.12 LSV polarization curve of the oxygen reduction reaction catalytic activity test of the cobalt-based sulfide catalytic material prepared in Example 3 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential in volts (V); the ordinate represents the current density in milliamperes per square centimeter (mA cm -2 ),like Fig.12 As shown, it can be concluded that the half-wave potential of the oxygen reduction reaction of the cobalt-based sulfide catalytic material prepared in Example 3 is 0.785 V (vs. RHE).
[0064] Fig.13 The LSV polarization curve of the oxygen evolution reaction catalytic activity test of the cobalt-based sulfide self-supporting catalytic material prepared in Example 3 of the present invention; wherein the abscissa represents the reversible hydrogen electrode potential in volts (V); the ordinate represents the current density in milliamperes per square centimeter (mA cm -2 ),like Fig.13 As shown, the cobalt-based sulfide self-supporting catalytic material prepared in Example 3 can be obtained at 10 mA·cm -2 The overpotential is 268 mV at a current density of .
[0065] In summary, under the same test conditions, the half-wave potential of the oxygen reduction reaction of the cobalt-based sulfide self-supporting catalytic materials prepared in Examples 1 to 3 is slightly lower than the half-wave potential of the oxygen reduction reaction of the commercial Pt / C precious metal catalyst, and the overpotential of the oxygen evolution reaction of the cobalt-based sulfide self-supporting catalytic materials prepared in Examples 1 to 3 is lower than the overpotential of the oxygen evolution reaction of the commercial RuO2 precious metal catalyst, demonstrating excellent bifunctional catalytic activity.
[0066] Test Example 4: Battery Performance Test of Cobalt-based Sulfide Self-supporting Catalytic Material Applied to the Battery Cathode of Zinc-air Battery The cobalt-based sulfide self-supporting catalytic material prepared in the above Example 1 was used as a zinc-air self-supporting air positive electrode, and the zinc-air battery assembled therefrom was subjected to battery performance tests such as discharge polarization curve and cycle life.
[0067] The assembly method of the aqueous zinc-air battery is as follows: the cobalt-based sulfide self-supporting catalytic material prepared in the above Example 1 is used as the positive electrode of the zinc-air electrode, the polished zinc sheet is used as the negative electrode of the battery, and a mixed solution of 6M potassium hydroxide and 0.2M zinc acetate is used as the electrolyte to assemble the aqueous zinc-air battery. As a reference, a commercial 20% Pt / C+RuO2 noble metal catalyst is dispersed in an isopropanol / Nafion solution, and then drop-coated onto a carbon cloth substrate with a loading of 1.3 mg·cm -2 , used as the positive electrode of zinc-air battery.
[0068] Fig.14The discharge polarization curve and power density curve of the zinc-air battery based on the cobalt-based sulfide self-supporting catalytic material obtained in the above specific example 1 are shown. Fig.14 It can be seen that the ultimate power density of the zinc-air battery assembled using the cobalt-based sulfide self-supporting catalytic material obtained in Example 1 reaches 89.24 mW·cm -2 The Zn-air battery assembled with commercial 20% Pt / C+RuO2 noble metal catalyst has a power of 108.49 mW·cm -2 It can be seen that the limiting power density of the zinc-air battery assembled with the cobalt-based sulfide self-supporting catalytic material obtained in this embodiment is close to the limiting power density of the zinc-air battery assembled with the commercial 20% Pt / C+RuO2 precious metal catalyst, which can meet the application scenarios of most portable devices or light electronic products.
[0069] Fig.15 The zinc-air battery assembled with the cobalt-based sulfide self-supporting catalytic material obtained in the above specific example 1 was -2 The charge and discharge cycle stability test is carried out under constant current density. Fig.15 As shown, the zinc-air battery using the cobalt-based sulfide self-supporting catalytic material prepared by the present invention has a stable cycle life of 450 h, while the zinc-air battery assembled with the commercial 20% Pt / C+RuO2 noble metal catalyst has a significant mutation in the charge-discharge platform only after 110 h of charge-discharge cycle, and finally fails due to severe attenuation. The test results show that the zinc-air battery assembled with the cobalt-based sulfide self-supporting catalytic material prepared by the present invention can maintain long-term stable charge and discharge performance during the stability test process, which is much higher than the charge and discharge stability of the zinc-air battery assembled with the commercial 20% Pt / C+RuO2 noble metal catalyst.
[0070] In summary, the cobalt-based sulfide self-supporting catalytic material prepared by the present invention has dual-functional catalytic performance of oxygen reduction and oxygen evolution. In the application of zinc-air batteries, the ultimate power density of zinc-air batteries assembled by cobalt-based sulfide self-supporting catalytic materials is comparable to the ultimate power density of zinc-air batteries assembled by commercial 20% Pt / C+RuO2 precious metal catalysts, proving that it has a wide range of application scenarios, and the cobalt-based sulfide self-supporting catalytic material also exhibits a more stable cycle life than traditional precious metal catalysts. Overall, the preparation method provided by the present invention has good economic and environmental benefits, and the prepared cobalt-based sulfide self-supporting catalytic material can be applied to energy storage and conversion devices such as rechargeable zinc-air batteries, and has high practical application value and market application prospects.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A cobalt-based sulfide self-supporting catalytic material, characterized in that: It includes a substrate and a Co9S8 / CuCo2S4 heterostructure loaded on the substrate.
2. The catalytic material according to claim 1, characterized in that The Co9S8 / CuCo2S4 heterostructure is a hollow tubular structure.
3. The catalytic material according to claim 1, characterized in that The loading amount of the Co9S8 / CuCo2S4 heterostructure on the substrate is 0.5~3 mg·cm -2 .
4. A method for preparing a cobalt-based sulfide self-supporting catalytic material, characterized in that: Includes steps: S1: dissolving a metal compound and urea in water at room temperature to obtain a mixed solution, wherein the metal compound is a cobalt metal compound and a copper metal compound; S2: placing the substrate in the mixed solution and reacting at a temperature of 80-150° C. for 4-12 hours to in-situ grow a double metal hydroxide precursor on the substrate; S3: placing the substrate with the double metal hydroxide precursor obtained in step S2 in a sulfide aqueous solution, and performing a hydrothermal sulfidation reaction at a temperature of 100-200°C for 3-12 hours to form a Co9S8 / CuCo2S4 heterostructure on the substrate, thereby obtaining the desired cobalt-based sulfide self-supporting catalytic material.
5. The method according to claim 4, characterized in that In step S1, the molar ratio of the metal compound to urea is 1:(0.5-10), and the molar ratio of the cobalt metal compound to the copper metal compound of the metal compound is 1:(0.05-0.5).
6. The method according to claim 4, characterized in that In step S1, the cobalt metal compound is any one of cobalt nitrate, cobalt chloride, cobalt acetate, cobalt sulfate and hydrates thereof; the copper metal compound is any one of copper nitrate, copper chloride, copper acetate, copper sulfate and hydrates thereof.
7. The method according to claim 4, characterized in that Before step S2 is performed, the substrate is pre-treated with an acidic solution.
8. The method according to claim 4, characterized in that In step S3, the sulfide is any one of sodium sulfide, thioacetamide, thiourea and hydrates thereof, and the concentration thereof is 0.05-0.5 mol / L.
9. A positive electrode of a battery, characterized in that: The method comprises the cobalt-based sulfide self-supporting catalytic material according to any one of claims 1 to 3.
10. A zinc-air battery, characterized in that: Comprising the battery positive electrode as claimed in claim 9.
Citation Information
Patent Citations
Carbon material-supported copper-cobalt bimetallic sulfide composite material and its preparation method and application in waste water treatment
CN106944098A
Cobalt-base multiphase catalytic material as well as preparation method and application thereof
CN109589990A
Preparation method of cobalt sulfide-molybdenum sulfide-nitrogen doped carbon composite electrode
CN113355693A
Copper-doped cobalt sulfide porous nanosheet / nickel foam electrode and preparation method and application thereof
CN114807963A
Iron-cobalt bimetal oxygen reduction electro-catalytic material as well as preparation method and application thereof
CN114843536A